2005
DOI: 10.1128/jcm.43.6.2756-2763.2005
|View full text |Cite
|
Sign up to set email alerts
|

Central European Dobrava Hantavirus Isolate from a Striped Field Mouse ( Apodemus agrarius )

Abstract: Dobrava virus (DOBV) is a hantavirus that causes hemorrhagic fever with renal syndrome (HFRS) inEurope. It is hosted by at least two rodent species, Apodemus flavicollis and A. agrarius. According to their natural hosts they form the distinct genetic lineages DOBV-Af and DOBV-Aa, respectively. We have now established a DOBV isolate named Slovakia (SK/Aa) from an A. agrarius animal captured in Slovakia. The complete S and M and partial L segment nucleotide sequences of the new isolate were determined. Phylogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 53 publications
3
57
1
Order By: Relevance
“…This particular virus lineage is named DOBV-Aa, and a cell culture isolate of DOBV-Aa has been generated (14,15). The severity of HFRS caused by DOBV-Aa in central Europe is mild to moderate, less severe than its clinical course in Balkan countries associated with the DOBV-Af variant hosted by A. fl avicollis (14,16,17).…”
Section: Hemorrhagic Fever With Renal Syndrome Caused By 2 Lineages Omentioning
confidence: 99%
See 2 more Smart Citations
“…This particular virus lineage is named DOBV-Aa, and a cell culture isolate of DOBV-Aa has been generated (14,15). The severity of HFRS caused by DOBV-Aa in central Europe is mild to moderate, less severe than its clinical course in Balkan countries associated with the DOBV-Af variant hosted by A. fl avicollis (14,16,17).…”
Section: Hemorrhagic Fever With Renal Syndrome Caused By 2 Lineages Omentioning
confidence: 99%
“…Strains from central Europe and European central Russia form the DOBV-Aa lineage, which is distinct from Saaremaa strains from northeastern Europe (12,15). DOBV ecology and evolution have recently become even more complex when DOBV was detected in an additional rodent host, A. ponticus (Caucasian wood mouse), captured in Sochi district, in the southern part of European Russia (21).…”
Section: Hemorrhagic Fever With Renal Syndrome Caused By 2 Lineages Omentioning
confidence: 99%
See 1 more Smart Citation
“…More than 10 000 cases of HFRS are reported annually worldwide, mostly in Asia and Europe [3,4] . Lethality ranges from 1% for Puumala virus (PUUV) and Seoul virus infections to approximately 15% for Hantaan (HTNV) virus infections [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Two Central European DOBV-Kurkino cell culture isolates from mice allowing in vitro studies currently exist, one from Slovakia (Klempa et al, 2005) and the other from Germany (Popugaeva et al, 2012). In vitro studies with the German isolate showed that the virus uses cellular β3 integrins and Decay Accelerating Factor as entry receptors as has also been shown for the highly pathogenic Hantaan virus.…”
Section: Dobrava-belgrade Virusmentioning
confidence: 92%